Innovative Technologies for Teaching 7th Grade Informatics and Information Technologies in General Education Schools - Karimova Zilola Botirovna (Genius Journals, 2025)
This article discusses the pressing issues of applying innovative technologies in teaching 7th-grade informatics and information technologies in general education schools. The article analyzes modern teaching methods, interactive lessons, virtual laboratories, and other innovative approaches. Based on the research results, practical recommendations are provided to enhance the effectiveness of teaching. This article serves as a valuable resource for teachers, researchers, and education specialists.
Keywords: Informatics; information technologies; interactive lessons